EVALUATION OF HOSEHOLD WASTEWATER AND THE POSSIBILITY OF ISOLATING IT FOR IRRIGATION IN THE CITIES OF RAMADI AND HADITHA - AL-Nuaymy, Wathib S.; Mohammed, Huthaifa Jaseem; Mohammed, Ahmed Marzoog (Diyala Agricultural Sciences Journal, 2020)
A field survey was carried out for the cities of Ramadi and Haditha, which included calculating water volumes and assessing their quality for the purpose of irrigation used in house according to the nature of their uses in the house. Data and samples were obtained in collaboration with volunteers from the college of Agriculture, Girls college of Education and some of the residents of Ramadi, of the Basic Education faculty and some of the people in Haditha, and the data and samples obtained were up to 200 samples. The study showed the possibility of isolating the water used for domestic purposes from the water cycles and the possibility of reusing it for agricultural purposes as it became clear that the wastewater other than the toilets fall within the category C3S1 according to the USA classification, while the FAO classification of high quality to cause salinity risk and he study also proved that at least 65% can be reclaimed for irrigation purposes, equivalent to 389382000 m3 ,which can be harvested at the national level is 6% water deficit in Iraq .